Pace & Pugh, Studying For History - Pennington, Loren (Teaching History: A Journal of Methods, 1997)
David Pace and Sharon Pugh have produced a work for the student taking his or her first college history course. The first three chapters give the student sound advice on getting oriented in this first course, discuss the "new" kinds of history now being taught in colleges and universities (in which the authors assume, not altogether correctly, that the student is unlikely to have encountered any of these "new" varieties in secondary school), suggest the best ways to manage energy, time, and mind, and stress the necessity of thinking like an historian. The last four chapters deal with the nuts and bolts of course work: reading, listening, and study strategies, preparing for and taking examinations, and writing papers. All this is done in a plain and simple style illustrated with homey examples.